Controlling spontaneous emission from perovskite nanocrystals with plasmonic cavity and silicon nanopillar - Tjahjana, Liliana (2024)
We show the modification of spontaneous emission rate and photoluminescence intensity by plasmonic and silicon nanostructures. Up to 5.4-fold enhancement of spontaneous emission rate of perovskite nanocrystals is demonstrated by simple metal-emitter-metal layer structure. Strong absorption is demonstrated in silicon nanopillar structure.